(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aimed to identify the role of teachers of the first cycle of basic education in developing health awareness among students in light of the Corona pandemic in the city of Lattakia, and to investigate the impact of the following research variables (sex, educational and educational qualification, and number of years of experience) for teachers on their role in developing health awareness among the pupils. To address the research problem, a questionnaire was used that contained (25) phrases, and the research sample included (304) male and female teachers for the academic year 2022/2023, and the descriptive approach was used. In order to judge the validity of the questionnaire, it was presented to a group of (7) arbitrators specialized in the Faculty of Education, Tishreen University. Its stability was confirmed by applying it to a reconnaissance sample of (36) male and female teachers, by calculating Cronbach’s alpha coefficient, which amounted to (0.914) and (0.946) by the Spearman-Brown coefficient. The research concluded that the role of the teachers of the first cycle of basic education in developing health awareness among students in light of the Corona pandemic in the city of Lattakia came to a moderate degree, and there were no statistically significant differences between the teachers’ answers about their role in developing health awareness among students according to the variables (sex, number of Years of experience), and the presence of statistically significant differences between teachers’ answers about their role in developing health awareness among students according to the variable (educational and educational qualification).